Attendance Without Presence: Measuring Cognitive Class Avoidance Among Students - Nagel, Arvid; Biedermann, Horst (Central European Journal of Educational Research, 2021)
While the term “school absenteeism” refers to a student’s withdrawal from the reach of classroom instruction, we explicitly opt for the term “class avoidance.” Existing studies on this phenomenon have primarily dealt with unauthorized physical absence from class. However, in our contribution, we extend the scope to cognitive absence. The behavior of students who are physically present but cognitively disengaged has largely been neglected in educational research thus far. This deficit stands in contrast to the widely accepted importance of cognitive activation in the classroom. The core of our contribution consists in the presentation and the construct validation of a newly developed scale for measuring cognitive class avoidance (inattention in class). We evaluated this measurement instrument in a cross-sectional study with a sample of 171 seventh- to ninth-grade students (M = 14.3 years, SD = .94). Our data confirmed a theoretically founded g-factor model. The results of the analysis point to a limited prevalence of cognitive class avoidance. Such forms of behavior were significantly more frequently reported by boys than by girls, however.